2022
DOI: 10.3390/ijms23105614
|View full text |Cite
|
Sign up to set email alerts
|

Specific Local Predictors That Reflect the Tropism of Endometriosis—A Multiple Immunohistochemistry Technique

Abstract: Ectopic endometrial epithelium associates a wide spectrum of symptomatology. Their evolution can be influenced by inflammatory and vascular changes, that affect not only the structure and cell proliferation rate, but also symptoms. This prospective study involved tissue samples from surgically treated patients, stained using classical histotechniques and immunohistochemistry. We assessed ectopic endometrial glands (CK7+, CK20−), adjacent blood vessels (CD34+), estrogen/progesterone hormone receptors (ER+, PR+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Malignant degeneration may occur under the influence of local inflammatory, vascular or hormonal factors that contribute to the development of atypical hyperplastic and subsequently malignant lesions. The malignant aspect must be carefully distinguished when there are deep infiltrating nodules or intracystic papillary projections [14]. E and A are not malignant disorders, but some characteristics are similar to cancer: they can develop local and distant foci, develop resistance to apoptosis and invade other tissues with subsequent damage [15].…”
Section: Morphological Characteristics Of Endometriosis and Adenomyosismentioning
confidence: 99%
See 3 more Smart Citations
“…Malignant degeneration may occur under the influence of local inflammatory, vascular or hormonal factors that contribute to the development of atypical hyperplastic and subsequently malignant lesions. The malignant aspect must be carefully distinguished when there are deep infiltrating nodules or intracystic papillary projections [14]. E and A are not malignant disorders, but some characteristics are similar to cancer: they can develop local and distant foci, develop resistance to apoptosis and invade other tissues with subsequent damage [15].…”
Section: Morphological Characteristics Of Endometriosis and Adenomyosismentioning
confidence: 99%
“…Histopathological examination is the mainstay for the final diagnosis of E or A and the extent of tissue proliferation. Classical histological staining, hematoxylin-eosin (HE), highlights endometrial glandular structures, the presence of peri-glandular stroma and the degree of atypical glandular transformation [14].…”
Section: Morphological Characteristics Of Endometriosis and Adenomyosismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, to differentiate between ectopic and eutopic endometrium, it is of paramount importance to obtain additional knowledge of the different types of endometriosis (peritoneal superficial endometriosis, ovarian endometriomas, and deep infiltrating endometriosis); in this context, an interesting study shed new lights on this topic, remarking how different phenotypes of endometriosis show an altered differential expression of genes and microRNAs in relation to adhesion and apoptosis pathways [ 4 ]. In addition, Istrate-Ofiţeru et al found increased vascularity (CD34+) in areas with abdominal endometriosis and CD3+-:T-lymphocytes, CD20+-:B-lymphocytes, CD68+:macrophages, and Tryptase+: mastocytes were abundant, especially in cases with adenomyosis as a marker of the proinflammatory microenvironment, and a significantly higher division index-(Ki67+) in areas with adenomyosis, and the inactivation of tumor suppressor genes-p53+ in areas with neoplastic changes [ 5 ].…”
mentioning
confidence: 99%